African Women: The Neglected Partners and ignored Resource (Impact: Journal of Transformation, 2019)
African women are often neglected by people who do not understand their potential. The effect of this has relinquished so many women from leadership positions in Africa and also leads to the view of women as second-class citizens who have little to contribute to national reforms in society. Research shows that few women are legislators in Africa. For instance, in Nigeria 5.6% and in Kenya 19.7 % of the legislators are women (Sow, 2016). The neglect of women is experienced in some families, communities, churches and in the political context. Conversely, the gender bias that women are second-class citizens has led to the violation of women’s rights and mistreatment of women in Africa (Kamau, 2017). Men and women are created to reflect God’s glory. Jointly, they were to be fruitful and multiply, fill the earth, subdue it, and have dominion over all things (Genesis 1:27). Women are gifted by God to contribute significantly to the development of the nation. From the interaction with newspapers and personal interview with a woman accused of witchcraft, the authors aver that some women in Africa are neglected for the following reasons: inability to bear children in their matrimonial homes (even when it is their husbands who are infertile), parochial African belief systems that see women as inferior to men, and false witchcraft accusations. According to the authors, there is need to curtail this neglect through sound Biblical teachings about men and women as co-partners created in God’s image, a provision of opportunities for women to reach their potential, and empowerment of women through education to contribute significantly to the society. The method used in this paper is a situational assessment technique. The authors examined real-life situations of neglect in the African context and responded to the issues critically.